Phospholipid and fatty acid composition of methanol-utilizing bacteria. - Goldberg, I (1977)
Differences in phospholipid and fatty acid composition were found among bacteria using the serine or the ribulose monophosphate pathway for the assimilation of C1 compounds. These differences might be used as an additional criterion for the classification of methanol-utilizing bacteria.